The documentary process and the briefer matrimonial process before the bishop –special processes in a case of nullity of the matrimonial - BARTCZAK, ADAM (Prawo Kanoniczne, 2019)
The Code of Canon Law, which was reformed in 2015, gives the opportunity to bring proceedings for the nullity of marriage in two special forms. The first is the documentary process. The briefer process before the bishop was introduced to the Code in 2015 for the Pope Francis. Both trials are a unique form of a nullity of marriage. A thorough analysis of them shows many differences, but also similarities. Particular attention deserves the person of a judge. In both trials, however, all basic guarantees of procedural justice are preserved: an independent and impartial judge, equality of parties and the right to defense.